'Toxgnostics': An unmet need in cancer medicine - Church, D; Kerr, R; Domingo, E; Rosmarin, D; Palles, C; Maskell, K; Tomlinson, I; Kerr, D (Nature Publishing Group, 2014)
If we were to summarize the rationale that underpins medical oncology in a Latin aphorism, it might be 'veneno ergo sum'; that is, I poison, therefore I am. The burden of chemotherapy-associated toxicity is well recognized, but we have relatively few tools that increase the precision of anticancer drug prescribing. We propose a shift in emphasis from the focussed study of polymorphisms in drug metabolic pathways in small sets of patients to broader agnostic analyses to systematically correlate germline genetic variants with adverse events in large, well-defined cancer populations. Thus, we propose the new science of 'toxgnostics' (that is, the systematic, agnostic study of genetic predictors of toxicity from anticancer therapy). © 2014 Macmillan Publishers Limited.